2016
DOI: 10.18632/oncotarget.8911
|View full text |Cite
|
Sign up to set email alerts
|

p75 neurotrophin receptor and pro-BDNF promote cell survival and migration in clear cell renal cell carcinoma

Abstract: p75NTR, a member of TNF receptor family, is the low affinity receptor common to several mature neurotrophins and the high affinity receptor for pro-neurotrophins. Brain-Derived Neurotrophic Factor (BDNF), a member of neurotrophin family has been described to play an important role in development and progression of several cancers, through its binding to a high affinity tyrosine kinase receptor B (TrkB) and/or p75NTR. However, the functions of these two receptors in renal cell carcinoma (RCC) have never been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 49 publications
(85 reference statements)
0
36
0
Order By: Relevance
“…Binding of BDNF to its major receptor, tropomyosin-related receptor kinase B (TrkB) with high affinity and specificity ( 27 ), caused the activation of multiple downstream signaling pathway, such as PI3K/AKT, RAS/ERK, PLC/PKC, AMPK/ACC and JAK/STAT pathways ( 28 ). Recently studies have demonstrated that BDNF was able to promote tumorigenesis and progression in several human malignancies, such as clear cell renal cell carcinoma ( 29 ), breast ( 30 ), colon cancer ( 31 ), colorectal cancer ( 32 ), and neuroblastoma ( 33 ), suggesting that BDNF was closely associated with tumor progression. For NSCLC, It was reported that the expression of BDNF was upregulated in NSCLC tissues, and was associated with poor prognosis in non-small cell lung cancer ( 34 ), and that BDNF facilitates tumorigenesis of NSCLC ( 35 ), and NSCLC metastasis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of BDNF to its major receptor, tropomyosin-related receptor kinase B (TrkB) with high affinity and specificity ( 27 ), caused the activation of multiple downstream signaling pathway, such as PI3K/AKT, RAS/ERK, PLC/PKC, AMPK/ACC and JAK/STAT pathways ( 28 ). Recently studies have demonstrated that BDNF was able to promote tumorigenesis and progression in several human malignancies, such as clear cell renal cell carcinoma ( 29 ), breast ( 30 ), colon cancer ( 31 ), colorectal cancer ( 32 ), and neuroblastoma ( 33 ), suggesting that BDNF was closely associated with tumor progression. For NSCLC, It was reported that the expression of BDNF was upregulated in NSCLC tissues, and was associated with poor prognosis in non-small cell lung cancer ( 34 ), and that BDNF facilitates tumorigenesis of NSCLC ( 35 ), and NSCLC metastasis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Optimal concentrations of exogenous BDNF and NTS were determined previously. 14 , 21 The non-peptide NTSR antagonist SR142948A (Tocris Biosciences, Bristol, UK) was used at 67 n M , 56 PTX (Sigma-Aldrich, St Louis, MO, USA) at 200 ng/ml 35 , 57 ; TrkB inhibitors were K252a (Alomone Labs) at 100 n M 58 , 59 or ANA12 (Tocris Biosciences) at 100 μ M . 60 …”
Section: Methodsmentioning
confidence: 99%
“…BDNF facilitates cancer metastasis via binding to its receptors, TrkB/ TrkC and/or p75NTR as demonstrated in breast [ 79 ], colorectal [ 80 , 81 ], clear cell renal cell carcinoma [ 82 ] and non-small cell lung cancer (NSCLC) [ 83 ]. The expression of TrkB associates with nodal metastasis and peritoneal metastasis; whereas, TrkC expression associates with liver metastasis in colorectal cancer patients [ 81 ].…”
Section: Role Of Perineural Invasion In Cancer Metastasismentioning
confidence: 99%